A Produção Do Conhecimento Nas Ciências Agrárias E Ambientais 5 2019
DOI: 10.22533/at.ed.88319260413
|View full text |Cite
|
Sign up to set email alerts
|

Teores Minerais Em Diferentes Cultivares De Maçãs Nas Safras De 2016/17 E 2017/18

Abstract: Brasil. 2. Meio ambiente -Pesquisa -Brasil. I. Zuffo, Alan Mario. II. Série. CDD 630 Elaborado por Maurício Amormino Júnior -CRB6/2422 O conteúdo dos artigos e seus dados em sua forma, correção e confiabilidade são de responsabilidade exclusiva dos autores.2019 Permitido o download da obra e o compartilhamento desde que sejam atribuídos créditos aos autores, mas sem a possibilidade de alterá-la de nenhuma forma ou utilizá-la para fins comerciais.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…As can be seen from Table 6, the results of the mineral composition of Norwegian apples are similar to those of other fruits grown in other apple/growing regions of the world [114,119,128]. Soil, fertilization and cultivars definitely influence composition, but mineral content has been found to vary not only between cultivars but also between years [129]. This has also been confirmed in Norway, where variations strongly depend on the year of cultivation, as climatic effects cause variation in the phenological development of apple trees and consequently in the mineral uptake capacity [130].…”
Section: Apple Fruit Mineral Content and Its Qualitysupporting
confidence: 59%
“…As can be seen from Table 6, the results of the mineral composition of Norwegian apples are similar to those of other fruits grown in other apple/growing regions of the world [114,119,128]. Soil, fertilization and cultivars definitely influence composition, but mineral content has been found to vary not only between cultivars but also between years [129]. This has also been confirmed in Norway, where variations strongly depend on the year of cultivation, as climatic effects cause variation in the phenological development of apple trees and consequently in the mineral uptake capacity [130].…”
Section: Apple Fruit Mineral Content and Its Qualitysupporting
confidence: 59%
“…The mineral composition of fruits is related not only to their nutritional quality and benefits to human health, but also to postharvest behavior, which may influence their susceptibility to physiological disorders and storage capacity (AMARANTE et al, 2012;SCHVEITZER et al, 2019). In a study with different apple cultivars using a wedge (flesh + skin) to assess the mineral composition of fruits, Schveitzer et al (2019) found variations in mineral content not only among cultivars, but also among years. According to the authors, these results may justify the variation in susceptibility to physiological disorders observed in cultivars and seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Mineral contents in apples vary depending on the cultivar, production cycle and growing region (AMARANTE et al, 2012;BRUNETTO et al, 2015;SCHVEITZER et al, 2019). In this sense, although there is available information about the average levels of minerals in 'Gala ' and 'Fuji' cultivars (AMARANTE et al, 2012), little is known about the mineral composition of cultivars recently developed in Brazil.…”
Section: Introductionmentioning
confidence: 99%